If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 = z + -6 Reorder the terms: -18 = -6 + z Solving -18 = -6 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. -18 + -1z = -6 + z + -1z Combine like terms: z + -1z = 0 -18 + -1z = -6 + 0 -18 + -1z = -6 Add '18' to each side of the equation. -18 + 18 + -1z = -6 + 18 Combine like terms: -18 + 18 = 0 0 + -1z = -6 + 18 -1z = -6 + 18 Combine like terms: -6 + 18 = 12 -1z = 12 Divide each side by '-1'. z = -12 Simplifying z = -12
| 15x+40=180 | | 9x+6=3(3x+2) | | 3z+2x+y=1 | | -z+2y+x=1 | | 15x+40= | | Z+2y-x=1 | | y=1.1x-2 | | F(x)=5x^4+2x+7 | | (-9.5+12.3)(-14-10.6)=x | | -5.55/(-0.5)=x | | (7-v)(4v+1)=0 | | 6a+2a+3a-5= | | (-8.94)(4.94)=x | | 1.318-5.3=x | | -11.7+(-15.98)=x | | 2x+y+3z=1 | | x-16=27 | | -11.7+(-15.98)= | | -6(x+7)-43=4-35 | | x/-9=-5-(-7) | | d=65*5 | | 9x+17-8x=-2-10 | | 13x+8y=1163 | | D=65mph*5hours | | 78y=11(7y+40) | | 8-8=10x+8x | | (3-z)(5z-7)=0 | | 7y-x=14 | | 19-16=x/-7 | | 5a^2b^2c-15abc^2=0 | | f(x)=100x-11x^2+8 | | -3x=4-(-5) |